2016
DOI: 10.1016/j.jvs.2016.03.414
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-bonded expanded polytetrafluoroethylene femoropopliteal bypass grafts outperform expanded polytetrafluoroethylene grafts without heparin in a long-term comparison

Abstract: These data show that the Propaten HePTFE graft offered significantly better long-term patency over the SePTFE graft, suggesting Propaten as the prosthetic graft of choice for bypasses to the femoropopliteal artery when autologous vein is unavailable or inappropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 32 publications
(35 reference statements)
2
32
0
1
Order By: Relevance
“…3), which were the antisymmetric and symmetric stretching vibration absorption peaks of CF 2 , respectively. Consistent peaks at 2300-2400 cm 21 were observed in the spectrum of heparin as well as the spectra of the modified ePTFE films. In addition, the characteristic peaks at 1024 cm 21 were attributed to the symmetric vibrational band of the sulfonic groups (AOSO 3 A) in heparin.…”
Section: Successful Construction Of Hep/col Multilayers and Immobilizsupporting
confidence: 64%
See 1 more Smart Citation
“…3), which were the antisymmetric and symmetric stretching vibration absorption peaks of CF 2 , respectively. Consistent peaks at 2300-2400 cm 21 were observed in the spectrum of heparin as well as the spectra of the modified ePTFE films. In addition, the characteristic peaks at 1024 cm 21 were attributed to the symmetric vibrational band of the sulfonic groups (AOSO 3 A) in heparin.…”
Section: Successful Construction Of Hep/col Multilayers and Immobilizsupporting
confidence: 64%
“…In addition, the characteristic peaks at 1024 cm 21 were attributed to the symmetric vibrational band of the sulfonic groups (AOSO 3 A) in heparin. Characteristic absorption peaks of the amide I band were observed at approximately 1653 cm 21 . Distinctive peaks, attributed to the NAH bending and CAN stretching vibrations of amide II, were observed at approximately 1558 cm 21 , suggesting that the assembled collagen retained its triple-helical structure.…”
Section: Successful Construction Of Hep/col Multilayers and Immobilizmentioning
confidence: 99%
“…Karen et al 4 reported a comparable 4 year primary patency between covered stent endograft and expanded politretrafluoroethylene (ePTFE) bypass graft (59% vs 58%; p=.807) for the treatment of SFA obstructive lesions > 25 cm in length. More recently, Samson 16 reported a primary patency of 74.5% at 5 years for new generation heparin-bonded ePTFE bypass, increasing to 85% when above the knee bypass was performed.…”
Section: Discussionmentioning
confidence: 99%
“…12) When performing femoropopliteal bypass surgeries, heparinbonded ePTFE grafts showed significantly better graft patency rates than non-heparin-bonded ePTFE grafts. 13) However, no report has compared the graft patency rates between heparin-bonded and non-heparin-bonded ePTFE grafts in AxFB. Furthermore, Samson et al 7) reported that 2 of 34 (5.9%) non-heparin-bonded ePTFE grafts and 3 of 42 (7.1%) heparin-bonded ePTFE grafts were thrombosed; therefore, they concluded that they could not demonstrate the superiority of heparin-bonded ePTFE grafts for AxFB.…”
Section: Discussionmentioning
confidence: 99%